Keberlanjutan Tempat Pengolahan Sampah Terpadu di Desa Tawangsari, Kabupaten Boyolali - Anindya Ayu Puspa Nugraheni; Widjonarko Widjonarko (Jurusan Perencanaan Wilayah dan Kota, 2019)
Tawangsari Village is one of the locations that has conducted integrated solid waste at the integrated solid waste treatment facility. At the end of 2014, the Village Government, assisted by the Provincial Government through the Satker PPLP Cipta Karya PU, manage built integrated solid waste treatment facility (including buildings and infrastructure for waste management) and officially operated it in early 2015. The Tawangsari integrated solid waste treatment facility is the first large solid waste treatment facility and is still considered to be operating. Even though this is considered so, it is still feared that the integrated solid waste treatment facility will not be able to run properly (sustainably) in the future. This concern can be explained by the discovery of initial problems such as service coverage that does not meet minimum PU standards (less than 200 households), the operation was halted for quite a long time in 2017, weak community participation and economically indicated to still depend on operational funding assistance from the Village Government. This study aims to determine the sustainability of integrated solid waste treatment facility in Tawangsari Village. The results of the analysis show that Tawangsari integrated solid waste treatment facility has less chance of sustainability due to the low volume of waste managed, the existence of financial problems, not all workers can be relied on to ensure that technical activities run regularly, the community has not been maximally involved in supporting integrated solid waste treatment facility and the ability to reduce waste is still in small quantities.